2017
DOI: 10.1152/jn.00321.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and intersegmental influences among central pattern generating networks in the walking system of the stick insect

Abstract: To efficiently move around, animals need to coordinate their limbs. Proper, context-dependent coupling among the neural networks underlying leg movement is necessary for generating intersegmental coordination. In the slow-walking stick insect, local sensory information is very important for shaping coordination. However, central coupling mechanisms among segmental central pattern generators (CPGs) may also contribute to this. Here, we analyzed the interactions between contralateral networks that drive the depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
53
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 59 publications
12
53
1
1
Order By: Relevance
“…In addition to 245 the intersegmental decrease, there was a strong increase in the intrasegmental coupling 246 in the mesothoracic ganglion (by factors of 2-20) and a decrease in connectivity in the 247 metathoracic ganglion (by a factor of 2). This is in agreement with [28] where the 248 authors could demonstrate that the mesothoracic ganglion showed intrasegmental 249 phase-coupling even in the isolated state, while the connection of the metathoracic 250 ganglion to the mesothoracic ganglion had to be present in order to detect robust 251 in-phase coupling in the metathoracic ganglion. The connectivity strengths were calculated for intervals that were pre-identified as phase-coupled by the PC approach.…”
supporting
confidence: 81%
“…In addition to 245 the intersegmental decrease, there was a strong increase in the intrasegmental coupling 246 in the mesothoracic ganglion (by factors of 2-20) and a decrease in connectivity in the 247 metathoracic ganglion (by a factor of 2). This is in agreement with [28] where the 248 authors could demonstrate that the mesothoracic ganglion showed intrasegmental 249 phase-coupling even in the isolated state, while the connection of the metathoracic 250 ganglion to the mesothoracic ganglion had to be present in order to detect robust 251 in-phase coupling in the metathoracic ganglion. The connectivity strengths were calculated for intervals that were pre-identified as phase-coupled by the PC approach.…”
supporting
confidence: 81%
“…In general, in fully or partly deafferented insects ipislateral neighboring legs fire in-phase, whereas in walking these legs typically show about anti-phase coupling. Supporting results for Carausius are presented by Mantziaris et al (2017), and Borgmann et al (2007, who recorded from the motor neurons activating the retractor muscles, and by Büschges et al (1995), who recorded from motor neurons of all three joints. Interestingly, corresponding results have been found for crustacea (Clarac and Chasserat 1979;Sillar et al 1987).…”
Section: Central Pattern Generatorsmentioning
confidence: 79%
“…However, as the behavioral data proposes that we deal with a continuous behavioral spectrum, this concept does not support a view of distinct motor schemas on the neuronal level (Graham (1972) for Carausius; Wosnitza et al (2013) for Drosophila; see also Mantziaris et al (2017) for discussion). Regular "gaits" only appear in the eye of the observer and it might therefore be misleading to assume that a controller has been evolved to produce separate gaits.…”
Section: Free Gait Controllers: Emergence Of Coordination Patternsmentioning
confidence: 96%
See 1 more Smart Citation
“…Behavioral experiments have revealed correlations between the positions of different legs in arthropods [29,45], but the underlying networks remain largely unknown. Work in locusts suggests that some direct neural connections between the legs may contribute to coordination during walking [3,46]. Therefore, in SimRoach2, the levator-depressor (CTr) CPGs between legs are connected and neural pathways were engineered to produce the observed behavior.…”
Section: Inter-leg Coordinationmentioning
confidence: 99%